PROSPEK PENGEMBANGAN INDUSTRI IKAN ASIN DI KOTA SIBOLGA - Panjaitan, kiki Maria Monalisa; Yusuf, Yusbar; Harahap, Azwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to find out the feasibility of the salted fish industry in Sibolga both in terms of financial aspect or aspects of marketing, as well as to find out the potential of marine and fishery of Sibolga. The conclusion that the salted fish Industry in Sibolga deserves to be on the run. angak obtained value NPV basis amounted to 7.963.367. For the value of the Benefit Cost Ratio (B/C Ratio), Internal Rate of Return (IRR), Revenue Cost Ratio (R/C Ratio) in a row, 29.43% 1,03028201, 2.183539381. While the resource return on investment or capital payback period analysis using retrieved 5 months 28 days, return the value of this investment belongs to very quickly from an estimated 5 years. In addition to the aspects of the financial aspects of the market also showed the feasibility of which can be seen from the value of the bid request, the value of the < whereas area marketing salted fish is not only limited in sibolga alone but also outside of the area of sibolga which means market share of this industry is already quite widespread. Moreover the potential of marine and fishery of sibolga is very large, even marine and fisheries sibolga may be mentioned as drivers of the economy in Sibolga.Keywords: Industrial Prospects, Benefit Cost Ratio, Net Present Value, and Internal Rate Of Return